Pengaruh Baby Swim Terhadap Perkembangan Motorik Bayi Usia 4 – 12 Bulan - Alfiani Alwi (Window of Public Health Journal, 2026)
Motor development during infancy is a crucial foundation for children's physical and cognitive development. Motor development delay in infants aged 4-12 months remains a problem that requires early stimulation. Baby swim is a form of early stimulation that utilizes the properties of water to stimulate muscle movement and neural coordination. This study aimed to analyze the effect of baby swim on the motor development of infants aged 4-12 months at Asyifa Baby Care Clinic Sengkang, Wajo Regency. The study employed a pre-experimental design with a one group pretest-posttest design. The study population consisted of all infants aged 4-12 months who participated in baby swim at the clinic. The sample comprised 30 infants selected using the total sampling technique. The baby swim intervention was conducted by a trained midwife following standard operating procedures for 10-15 minutes in warm water at 38-40°C using a neck ring. Motor development was measured using the Pre-Screening Developmental Questionnaire (KPSP) before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of p<0.05. Before the intervention, the majority of infants (80.0%) were in the questionable development category with the language development being the most delayed aspect. After the intervention, a significant improvement was observed, with 73.3% of infants achieving normal development status, particularly in the fine motor development. The Wilcoxon test showed a significant effect of baby swim on infant motor development (p=0.000; p<0.05). Baby swim is an effective early stimulation intervention for improving motor development in infants aged 4-12 months.